Evaluación de las prácticas de seguridad industrial que se aplican en las PYMES afiliadas a la asociación de empresarios del norte de Quito para optimizar la administración de seguridad y salud ocupacional, y propuesta de un modelo de capacitación en sistemas de gestión de la seguridad para la gerencia. - Soria Romero, Ernesto Fabián (2015)
Integral Management of a company includes the application of modera management tools and techniques for managing Health and Safety at work. The ability to manage both managers as partners, aimed at preventing accidents and occupational health monitoring is an ongoing challenge for employers committed to your organization's policies and legal requirements of the country. The implementation of effective practices for managing health and safety can provide safe work sites, minimizing the possibility of accidents. A management system for health and safety to optimize the resources of a company and promotes continuous improvement. Research in several SMEs affiliated to the AEN-Q, failed to identify and appraise industrial safety practices that apply in determining the effectiveness of these to cover the administrative and technical programs to protect workers, aligning them with the management styles modern administration. The methodology used for research, was based on the collection of information through a survey of managers of SMEs, and observation of organizational behavior within each company. The result allowed to prioritize the issues necessary to form a training module on Safety Management Systems for management, aligning its activities to a modern management model, according to the size of your company's orientation towards development work in an environment insurance, to ensure the health and welfare of their workers. As a result, the employer can demónstrate continuous improvement within your organization and outside it to revamp its brand image as a result of compliance with its legal obligations.